Effects of Omega-3 Fatty Acids in Prevention of Early Preterm Delivery: A Systematic Review and Meta-analysis of Randomized Studies. Issue 7 (July 2016) - Kar, Sumit; Wong, Min; Rogozinska, Ewelina; Thangaratinam, Shakila
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2016;198:40–46) Gestational age at delivery is the single most important determinant of survival and long-term neurodevelopment of the newborn. Early preterm infants, especially those born before 34 weeks of gestation, often need prolonged intensive care for prematurity-related morbidity and long-term support for neurodevelopmental problems.